The Magnetostratigraphy and the Age of So’a Basin Fossil-Bearing Sequence, Flores, Indonesia - Yurnaldi, Dida; Setiawan, Ruly; Patriani, Emma Yan (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.3.221-234Three fossil-bearing intervals have been recognized in the Pleistocene So’a Basin, with the upper one holding important evidence of hominin fossils. The sequence also contains numerous in situ stone artifacts and fossils of other vertebrate taxa. Therefore, multiple dating techniques are crucial to secure the age of the fossil and artifact-bearing layers, especially the one with the hominin remains. This paper deals with the palaeomagnetic dating of the So’a Basin sequence to assist other dating methods that have been applied, and to refine the chronostratigraphy of the area. Palaeomagnetic sampling was conducted in four sections along a west to east transect. Four magnetozones can be recognized, consisting of two reverse and two normal polarity zones. By using the available radiometric ages as a guide and comparing the So’a Basin magnetostratigraphy with the Standard Geomagnetic Polarity Time Scale (GPTS), it became clear that both reverse magnetozones are part of the Matuyama Chron, while the normal magnetozones are the Jaramillo subchron and the Brunhes Chron. These palaeomagnetic dating results support the available radiometric dates and refine the age of the fossil-bearing deposits of the So’a Basin.